Traces of musical heritage in Faroese popular music - Atli Kárason Petersen 1963- (2017)
Fascination of the term “National Identity”, and more precisely “National Musical Identity”, have initiated this study. In an attempt to shed some light on this topic, a number of questions have been addressed: Is there a link between the traditional music and the popular music of today in the Faroe Islands? Is it possible to find traces of the musical heritage in Faroese popular music? And do the Faroese artists recognize this heritage, are they using it consciously, or is it implemented subconsciously? Through interviews with Faroese artists, compared with analysis of their music which then were held against identifiers extracted from transcriptions of the traditional music it has been attempted to find similarities in both the old and the new. Traces have been found, yet perhaps not in numbers large enough to draw any definite conclusions, but still enough to continue the search for more